ผลกระทบของนโยบายการปรับเพิ่มเงินเดือนปริญญาตรีต่อองค์กรปกครองท้องถิ่น จังหวัดเชียงใหม่ - ศตคุณ ไชยพล (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
The study “Impacts of Policy Implementation in Bachelor Degree Monthly Salaries Increase towards Local Administration, Chiang Mai Province” aimed to 1) study the impacts of the implementation of the government’s 15,000 baht minimum monthly salary policy on Chiang Mai local administrations, and 2) investigate problems and obstacles in implementing the government’s 15,000 baht minimum monthly salary policy of Chiang Mai local administrations. This study employed qualitative research methodology and survey research methodology by using documentary research and questionnaire survey. The questionnaire respondents were 417 administrators, deputies, and officials from 139 Chiang Mai local administrations. Moreover, the data was analyzed by descriptive data analysis method. The data revealed that the 15,000 baht minimum monthly salary policy, a public policy, was formulated by the government as the activity frameworks which aimed at enhancing the quality of life of the citizens according to the state of the society. In addition, since a political system and the citizens have been intertwined, a public policy, established by the government as a political result, was developed to solve public’s problems. The policy was supported through processes, plans, and projects, or by the different organizations. Furthermore, it was found that there were various authorities in establishing the increase of monthly salary policy which affected the ability of the organizations to implement the policy to conform to the authorities in the local administrations. This relied on limited resources to manage the organizations to achieve the objectives which depended heavily on the ability and income of each organization. However, because of different sizes of the local administrations in Chiang Mai, the management of each organization was different according to its context which, consequently, affected the local administrations in different aspects. In terms of solutions to the problems, it was found that the government’s monthly salary increase policy had both positive and negative impacts on the local administrations because the implementation of the policy caused the imbalanced of the organizations’ income and expenses. Though this top-down policy had to be followed, according to bureaucratic system, the local administrations could manage the problems by employing the decentralization of local administration. Therefore, in order to implement the policy which increased the long term expenses, there should be a consideration process based on authorities and context of each community. In addition, the administrators of the local administrations should equally treat the staff members and be aware of the proportion of the amount of work to the staff. They should also study local contexts and other factors to find out methods in implementing the policy. For the future research, it can be suggested that since this study has investigated the impacts of the implementation of the government’s monthly salary increase policy on the local administrations in Chiang Mai, there should be more studies on the guidelines or frames in implementing the policy in order to similarly establish the policy in different communities with different contexts.